2020
DOI: 10.1177/2158244020914576
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Distance and Descriptive Norms on Environmental Behaviors: A Cross-Cultural Examination of Construal-Level Theory

Abstract: Rapid urbanization has beset sustainable consumption. Although many countries are increasingly taking pro-environmental stances, most countries continue to have a low recycling rate and a high littering rate. This study examines the effect of temporal distance as a part of Construal-Level Theory and descriptive norms on pro- and contra-environmental behaviors (i.e., recycling and littering) cross-culturally. Participants were recruited from the United States and South Korea, and randomly assigned to one of fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Third, we only recruited mainland Chinese as study participants because the data was collected during Covid-19 pandemic period, and at that time, China is one of the few countries having little restrictions on domestic travel. Previous research showed that culture might have an impact on perception of time (Park et al , 2020). A future event was more likely to be represented in more abstract terms for individuals with independent self-construal than interdependent self-construal (Spassova and Lee, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Third, we only recruited mainland Chinese as study participants because the data was collected during Covid-19 pandemic period, and at that time, China is one of the few countries having little restrictions on domestic travel. Previous research showed that culture might have an impact on perception of time (Park et al , 2020). A future event was more likely to be represented in more abstract terms for individuals with independent self-construal than interdependent self-construal (Spassova and Lee, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The energy consumed by the construction industry accounts for 40% of the global energy consumption, which is seriously affecting our living environment (Bang et al, 2021). The study results provide insights for the transport sector to establish sustainable urban traffic management policies and strategies to increase the share of zero emission and low emission modes of transport (Park et al, 2020).…”
Section: Literature Co-citation Analysis and Knowledge Base Identific...mentioning
confidence: 95%
“…This construal variation is attributed to the concept of psychological distance, that is, the degree of proximity that a person has from an object or event. According to CLT, psychological distance has four dimensions: spatial, temporal, social and hypotheticality (uncertainty) [51][52][53]. Spatial distance refers to whether individuals perceive that an object/event is geographically faraway or nearby [54].…”
Section: Construal Level Theory Spatial Distance and Csr Beneficiariesmentioning
confidence: 99%